Analysis of Wheel Squeal and Flanging on Curved Railway Tracks - Kim, Jae Chul; Yun, Yang Soo; Noh, Hee-Min (International journal of precision engineering and manufacturing, 2019)
When a railway vehicle moves over a sharply curved section of track, intense high-frequency noises sometimes occur. These are potentially a source of annoyance to those living adjacent to railway tracks. To efficiently identify measures appropriate to reduce curve squeal, it is important to determine the dominant noise type. However, it is difficult to analyze the various noises made over curved sections of railway using general noise measurements. In this study, we analyzed squealing and flange noises using various experimental approaches. We first investigated the noise characteristics of the railway vehicle via structural analysis of the wheel. It was confirmed that a wheel has various natural frequencies and eigenmodes in the high frequency range, i.e. over 1000 Hz. A roller rig test was performed to measure and investigate the characteristics of the noise generated when an actual wheel and the curved section of the railway track come in contact with each other. In this experiment the squeal and the flange noises, in particular, were reproduced by adjustments made to the lateral angle and vertical force, respectively. Results confirmed that the squealing noise occurs in the high frequency region and the flange noise occurs in various modes. A study was also conducted to measure and analyze the noise in the actual curved section of an urban railway. By comparing the frequency analysis and the natural frequency analysis of the noise that was actually measured, the mode by which the wheel caused the squealing noise was confirmed. Furthermore, the influence of the noise generated inside and outside the curved section of the track was investigated based on velocity, and the influence of the former on the noise generated was also examined. This study provides information on the squeal and flange noises generated when a railway vehicle moves over a curved section of a railway using various experimental approaches.